ANALISIS KINERJA KEUANGAN PT. “A” INDONESIA TAHUN 2007 – 2012 - Chairina Utami; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to identify and analyze financial performance of PT.  “A”  Indonesia in 2007 - 2012 assessed by the ratio of liquidity, solvency, profitability, and activity.  This study is a descriptive analysis research by using a quantitative approach. This study uses quantitative data as the only type of data. Based on the source, the data used in this study is primary data, the data obtained directly from the PT. "A" Indonesia. The results of  the company's financial performance in terms of liquidity (current ratio) shows there is a risk for the company in the ability  to repay short-term liabilities. The financial performance of  the company in terms of solvency (debt to equity ratio and debt to total assets ratio) shows  that the company has continued to decline in the ability to pay off long-term liabilities from 2007 until 2010. The company's financial  performance in term  of profitability (return on equity and return on assets) shows that the company started to improve and increase in the rate of return on earnings through the use of capital and total assets after the acquisition. But on average, the ratio of profitability is not good. The financial performance of  the company in terms  of  activity (fixed asset turnover, total asset turnover, and accounts receivable turnover) shows that the company is getting better at using its assets effectively to increase revenue. This is evidenced by the results of all  calculations of the  activity  ratio that  is  increasing from year to year.Keywords: Financial Performance, Financial Ratio Analysis, Liquidity Ratio, Solvency Ratio, Profitability Ratio, Activity Ratio.